Profile of ezogabine (retigabine) and its potential as an adjunctive treatment for patients with partial-onset seizures - Weisenberg, Judith LZ (Dove Medical Press, 2011)
Epilepsy is a common disease with significant morbidity and mortality. Approximately one-third of patients with epilepsy are refractory to available seizure medications, emphasizing the need to develop better drugs with novel mechanisms of action. Ezogabine, also known as retigabine, is a new potential adjunctive treatment for adults with intractable partial seizures. Ezogabine has a unique mechanism of action consisting of activating KCNQ2/3 (Kv7) potassium channels. Ezogabine has undergone a number of Phase II and III trials demonstrating efficacy at 600,900 and 1200 mg/day in a dose-dependent fashion. The most common adverse events with ezogabine are central nervous system effects, particularly dizziness and somnolence. Urologic symptoms, particularly urinary retention, represent a rare but unique side effect of ezogabine. Ezogabine is predominantly metabolized via glucuronidation. Its half-life is 8 hours, suggesting a need for three-times-a-day administration. Ezogabine exhibits minimal interactions with other seizure medications, except possibly lamotrigine. Ezogabine has potential for clinical applications in other medical conditions beyond epilepsy, such as neuropathic pain, neuromyotonia, and bipolar disease, but these are based primarily on experimental models.